Algebra


  1. If x = 3 + 2√2 , then the value of
    x6 + x4 + x2 + 1
    is equal to
    x3










  1. View Hint View Answer Discuss in Forum

    Expression =
    x6 + x4 + x2 + 1
    x3

    Expression =
    x6
    +
    x4
    +
    x2
    +
    1
    x3x3x3x3

    Expression = x3 + x +
    1
    +
    1
    xx3

    Expression = x3 +
    1
    + x +
    1
    x3x

    Expression = x +
    1
    3 - 3x +
    1
    + x +
    1
    xxx

    Expression = x +
    1
    3 - 2 x +
    1
    ---(i)
    xx

    Now, x = 3 + 2√2
    1
    =
    1
    x3 + 2√2

    =
    1
    ×
    3 - 2√2
    3 + 2√23 - 2√2

    1
    =
    3 - 2√2
    x9 - 8

    ∴ x +
    1
    = 3 + 2√2 + 3 - 2√2 = 6
    x

    ∴ Expression = (6)3 - 2 × 6 = 216 –12 = 204

    Correct Option: D

    Expression =
    x6 + x4 + x2 + 1
    x3

    Expression =
    x6
    +
    x4
    +
    x2
    +
    1
    x3x3x3x3

    Expression = x3 + x +
    1
    +
    1
    xx3

    Expression = x3 +
    1
    + x +
    1
    x3x

    Expression = x +
    1
    3 - 3x +
    1
    + x +
    1
    xxx

    Expression = x +
    1
    3 - 2 x +
    1
    ---(i)
    xx

    Now, x = 3 + 2√2
    1
    =
    1
    x3 + 2√2

    =
    1
    ×
    3 - 2√2
    3 + 2√23 - 2√2

    1
    =
    3 - 2√2
    x9 - 8

    ∴ x +
    1
    = 3 + 2√2 + 3 - 2√2 = 6
    x

    ∴ Expression = (6)3 - 2 × 6 = 216 –12 = 204


  1. If x +
    1
    = 3 , then the value of
    3x2 - 4x + 3
    is
    xx2 - x + 1










  1. View Hint View Answer Discuss in Forum

    Given , x +
    1
    = 3
    x

    Expression =
    3x2 - 4x + 3
    x2 - x + 1

    Expression =
    (3x2 - 3x + 3) - x
    x2 - x + 1

    Expression =
    3(x2 - x + 1)
    -
    x
    x2 - x + 1x2 - x + 1

    Expression = 3 -
    1
    x - 1 +
    1
    x

    Expression = 3 -
    1
    x +
    1
    + 1
    x

    Expression = 3 -
    1
    = 3 -
    1
    3 - 12

    Expression =
    6 - 1
    =
    5
    22

    Correct Option: C

    Given , x +
    1
    = 3
    x

    Expression =
    3x2 - 4x + 3
    x2 - x + 1

    Expression =
    (3x2 - 3x + 3) - x
    x2 - x + 1

    Expression =
    3(x2 - x + 1)
    -
    x
    x2 - x + 1x2 - x + 1

    Expression = 3 -
    1
    x - 1 +
    1
    x

    Expression = 3 -
    1
    x +
    1
    + 1
    x

    Expression = 3 -
    1
    = 3 -
    1
    3 - 12

    Expression =
    6 - 1
    =
    5
    22



  1. If x = 997, y = 998 and z = 999, then the value of x2 + y2 + z2 – xy – yz – zx is









  1. View Hint View Answer Discuss in Forum

    x = 997 , y = 998 , z = 999
    ∴ x – y = 997 – 998 = –1
    y – z = 998 – 999 = –1
    z – x = 999 – 997 = 2

    ∴ x2 + y2 + z2 – xy – yz – zx =
    1
    [ 2x2 + 2y2 + 2z2 – 2xy – 2yz – 2zx ]
    2

    ⇒ x2 + y2 + z2 – xy – yz – zx =
    1
    [ x2 + y2 – 2xy + y2 + z2 – 2yz + z2 + x2 – 2zx ]
    2

    ⇒ x2 + y2 + z2 – xy – yz – zx =
    1
    [ (x - y)2 + (y - z)2 + (z - x)2 ]
    2

    ⇒ x2 + y2 + z2 – xy – yz – zx =
    1
    [ (-1)2 + (-1)2 + (2)2 ]
    2

    ⇒ x2 + y2 + z2 – xy – yz – zx =
    1
    [ 1 + 1 + 4 ]
    2

    ⇒ x2 + y2 + z2 – xy – yz – zx =
    1
    × 6 = 3
    2

    Correct Option: D

    x = 997 , y = 998 , z = 999
    ∴ x – y = 997 – 998 = –1
    y – z = 998 – 999 = –1
    z – x = 999 – 997 = 2

    ∴ x2 + y2 + z2 – xy – yz – zx =
    1
    [ 2x2 + 2y2 + 2z2 – 2xy – 2yz – 2zx ]
    2

    ⇒ x2 + y2 + z2 – xy – yz – zx =
    1
    [ x2 + y2 – 2xy + y2 + z2 – 2yz + z2 + x2 – 2zx ]
    2

    ⇒ x2 + y2 + z2 – xy – yz – zx =
    1
    [ (x - y)2 + (y - z)2 + (z - x)2 ]
    2

    ⇒ x2 + y2 + z2 – xy – yz – zx =
    1
    [ (-1)2 + (-1)2 + (2)2 ]
    2

    ⇒ x2 + y2 + z2 – xy – yz – zx =
    1
    [ 1 + 1 + 4 ]
    2

    ⇒ x2 + y2 + z2 – xy – yz – zx =
    1
    × 6 = 3
    2


  1. If a +
    1
    = √3 ,then the value
    of a18 + a12 + a6 + 1 is
    a










  1. View Hint View Answer Discuss in Forum

    Using Rule 1 and 8,

    a +
    1
    = √3
    a

    On squaring both sides ,
    ⇒ a2 +
    1
    + 2 = 3
    a2

    ⇒ a2 +
    1
    = 3 – 2 = 1
    a2

    On cubing both sides,
    a2 +
    1
    3 = (1)3
    a2

    ⇒ a6 +
    1
    + 3a2 +
    1
    = 1
    a6a2

    ⇒ a6 +
    1
    = 1 - 3 = -2
    a6

    a12 + 1
    = -2
    a6

    ⇒ a12 + 2a6 + 1 = 0
    ⇒ ( a6 + 1 )2 = 0
    ⇒ a6 + 1 = 0
    ∴ Expression = a18 + a12 + a6 + 1
    Expression = a12(a6 + 1) + 1(a6 + 1) = 0

    Correct Option: A

    Using Rule 1 and 8,

    a +
    1
    = √3
    a

    On squaring both sides ,
    ⇒ a2 +
    1
    + 2 = 3
    a2

    ⇒ a2 +
    1
    = 3 – 2 = 1
    a2

    On cubing both sides,
    a2 +
    1
    3 = (1)3
    a2

    ⇒ a6 +
    1
    + 3a2 +
    1
    = 1
    a6a2

    ⇒ a6 +
    1
    = 1 - 3 = -2
    a6

    a12 + 1
    = -2
    a6

    ⇒ a12 + 2a6 + 1 = 0
    ⇒ ( a6 + 1 )2 = 0
    ⇒ a6 + 1 = 0
    ∴ Expression = a18 + a12 + a6 + 1
    Expression = a12(a6 + 1) + 1(a6 + 1) = 0



  1. If a +
    1
    2 = 3 , then the value of a3 +
    1
    is
    aa3










  1. View Hint View Answer Discuss in Forum

    Using Rule 8,

    a +
    1
    2 = 3
    a

    ⇒ a +
    1
    = √3
    a

    On cubing both sides,
    a +
    1
    3 = (√3)3
    a

    ⇒ a3 +
    1
    + 3a +
    1
    = 3√3
    a3a

    ⇒ a3 +
    1
    + 3 × √3 = 3√3
    a3

    ⇒ a3 +
    1
    = 3√3 - 3√3 = 0
    a3

    Correct Option: A

    Using Rule 8,

    a +
    1
    2 = 3
    a

    ⇒ a +
    1
    = √3
    a

    On cubing both sides,
    a +
    1
    3 = (√3)3
    a

    ⇒ a3 +
    1
    + 3a +
    1
    = 3√3
    a3a

    ⇒ a3 +
    1
    + 3 × √3 = 3√3
    a3

    ⇒ a3 +
    1
    = 3√3 - 3√3 = 0
    a3